Ảnh hưởng của một số điều kiện tổng hợp lên cấu trúc của hệ xúc tác có mao quản trung bình spinel NiAl - Ngà và cộng sự, Nguyễn Kim (Vietnam Journal of Chemistry, 2014)
In order to prepare mesoporous nickel aluminate spinel with high surface area two factors: calcinations temperature and thermal treatment were investigated in this study. The prepared spinels were characterized by a variety of techniques such as XRD, TPR-H2, TEM and nitrogen adsorption. The obtained results showed that, not depending on the synthesis conditions the main phase as NiAl2O4 spinel was formed over all of the samples, however, their BET surface areas were considerably effected by changing the synthesis conditions.